2012
DOI: 10.1136/annrheumdis-2012-201472
|View full text |Cite
|
Sign up to set email alerts
|

Risk of sick leave and disability pension in working-age women and men with knee osteoarthritis

Abstract: Subjects with doctor-diagnosed knee OA have an almost twofold increased risk of sick leave and about 40-50% increased risk of disability pension compared with the general population. About 2% of all sick days in society are attributable to knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
100
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 22 publications
2
100
0
4
Order By: Relevance
“…23 Twelve studies (71%) evaluated subjects with a self-diagnosis of knee osteoarthritis7 18 24–26 or knee pain20 27–32 while five studies (29%) confirmed the presence of knee osteoarthritis by a clinical diagnosis 22 23 33–35. Seven studies (47%)7 23 24 29 32 33 35 conducted population-based surveys or used population registries, while five studies (29%)18 22 25 26 34 recruited participants from clinics and five studies (29%) were occupation-specific cohorts 20 27 28 30 31…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…23 Twelve studies (71%) evaluated subjects with a self-diagnosis of knee osteoarthritis7 18 24–26 or knee pain20 27–32 while five studies (29%) confirmed the presence of knee osteoarthritis by a clinical diagnosis 22 23 33–35. Seven studies (47%)7 23 24 29 32 33 35 conducted population-based surveys or used population registries, while five studies (29%)18 22 25 26 34 recruited participants from clinics and five studies (29%) were occupation-specific cohorts 20 27 28 30 31…”
Section: Resultsmentioning
confidence: 99%
“…There were 10 (59%) cross-sectional studies7 24 25 27 29–33 35 and 5 (29%) prospective cohort studies: three with a 12-month follow-up,20 23 28 one with a 2-year follow-up18 and the other with a 12-week follow-up 34. The other 2 (12%) studies were retrospective in design 22 26.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations